Modern cancer therapy: cryoablation meets immune checkpoint blockade - Liu, Qi; Zhang, Chunyang; Chen, Xuxin; Han, Zhihai (Frontiers in Oncology, 2024)
Cryoablation, as a minimally invasive technology for the treatment of tumors, destroys target tumors with lethal low temperatures. It simultaneously releases a large number of tumor-specific antigens, pro-inflammatory cytokines, and nucleoproteins, known as “danger signals”, activating the body’s innate and adaptive immune responses. However, tumor cells can promote the inactivation of immune effector cells by reprogramming immune checkpoints, leading to the insufficiency of these antigens to induce an immune response capable of eradicating the tumor. Immune checkpoint blockers rejuvenate exhausted T cells by blocking immune checkpoints that induce programmed death of T cells, and are therefore considered a promising therapeutic strategy to enhance the immune effects of cryoablation. In this review, we provide a detailed explanation of the immunological mechanisms of cryoablation and articulate the theoretical basis and research progress of the treatment of cancer with cryoablation combined with immune checkpoint blockers. Preliminary data indicates that this combined treatment strategy exhibits good synergy and has been proven to be safe and effective.